Laboratory study on the behaviour of spent AA household alkaline batteries in incineration - Almeida, Manuel F. (2011)
The quantitative evaluation of emissions from incineration is essential when Life Cycle Assessment (LCA) studies consider this process as an end-of-life solution for some wastes. Thus, the objective of this work is to quantify the main gaseous emissions produced when spent AA alkaline batteries are incinerated. With this aim, batteries were kept for 1 h at 1273 K in a refractory steel tube hold in a horizontal electric furnace with temperature control. At one end of the refractory steel tube, a constant air flow input assures the presence of oxygen in the atmosphere and guides the gaseous emissions to a filter system followed by a set of two bubbler flasks having an aqueous solution of 10% (v/v) nitric acid. After each set of experiments, sulphur, chlorides and metals (As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Sb, Tl and Zn) were analyzed in both the solutions obtained from the steel tube washing and from the bubblers. Sulphur, chlorides and metals were quantified, respectively, using barium sulfate gravimetry, the Volhard method and atomic absorption spectrometry (AAS). The emissions of zinc, the most emitted metal, represent about 6.5% of the zinc content in the batteries. Emissions of manganese (whose oxide is the main component of the cathode) and iron (from the cathode collector) are negligible when compared with their amount in AA alkaline batteries. Mercury is the metal with higher volatility in the composition of the batteries and was collected even in the second bubbler flask. The amount of chlorides collected corresponds to about 36% of the chlorine in the battery sleeve that is made from PVC. A considerable part of the HCl formed in PVC plastic sleeve incineration is neutralized with KOH, zinc and manganese oxides and, thus, it is not totally released in the gas. Some of the emissions are predictable through a thermodynamic data analysis at temperatures in the range of 1200–1300 K taking into account the composition of the batteries. This analysis was done for most of potential reactions between components in the batteries as well as between them and the surrounding atmosphere and it reasonably agrees the experimental results. The results obtained show the role of alkaline batteries at the acid gases cleaning process, through the neutralization reactions of some of their components. Therefore, LCA of spent AA alkaline batteries at the municipal solid waste (MSW) incineration process must consider this contribution.